Spatiotemporal dynamics of responses to biological motion in the human brain - Chang, D. H. F.; Troje, N. F.; Ikegaya, Y.; Fujita, I.; Ban, H. (Cortex, 2021)
We sought to understand the spatiotemporal characteristics of biological motion perception. We presented observers with biological motion walkers that differed in terms of form coherence or kinematics (i.e., the presence or absence of natural acceleration). Participants were asked to discriminate the facing direction of the stimuli while their magnetoencephalographic responses were concurrently imaged. We found that two univariate response components can be observed around ~200 msec and ~650 msec post-stimulus onset, each engaging lateral-occipital and parietal cortex prior to temporal and frontal cortex. Moreover, while univariate responses show biological motion form-specificity only after 300 msec, multivariate patterns specific to form can be well discriminated from those for local cues as early as 100 msec after stimulus onset. By finally examining the representational similarity of fMRI and MEG patterned responses, we show that early responses to biological motion are most likely sourced to occipital cortex while later responses likely originate from extrastriate body areas.